Rho and Rap guanosine triphosphatase signaling in B cells and chronic lymphocytic leukemia. Issue 9 (September 2014) - Mele, Silvia; Devereux, Stephen; Ridley, Anne J.
Abstract Chronic lymphocytic leukemia (CLL) cells proliferate predominantly in niches in the lymph nodes, where signaling from the B cell receptor (BCR) and the surrounding microenvironment are critical for disease progression. In addition, leukemic cells traffic constantly from the bloodstream into the lymph nodes, migrate within lymphatic tissues and egress back to the bloodstream. These processes are driven by chemokines and their receptors, and depend on changes in cell migration and integrin-mediated adhesion. Here we describe how Rho and Rap guanosine triphosphatases (GTPases) contribute to both BCR signaling and chemokine receptor signaling, particularly by regulating cytoskeletal dynamics and integrin activity. We propose that new inhibitors of BCR-activated kinases are likely to affect CLL cell trafficking via Rho and Rap GTPases, and that upstream regulators or downstream effectors could be good targets for therapeutic intervention in CLL.